Customer Service: Empowerment and EntrapmentCustomer Service: Empowerment and Entrapment, edited by SturdyAndrew, GrugulisIrena and WillmottHugh Hampshire, UK: Palgrave, 2001. - Bowen, David (Academy of Management Review, 2004)
The article reviews the book ?Customer Service: Empowerment and Entrapment,? edited by Andrew Sturdy, Irena Grugulis and Hugh Willmott.